Effect of the Interval of Application of Artificial Ventilation System on Drying Duration of Seedless Grapes in Shield Drying (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article describes the results of research on the agrobiological characteristics of kishmishbop grape varieties suitable for drying. In this, the main indicators of the kishmishbop grape varieties selected for the experiments were analyzed. As a result of the research, scientifically based conclusions were made.